Enhancement of plant growth in lentil (Lens culinaris) under salinity stress by exogenous application or seed priming with salicylic acid and hydrogen peroxide. - Amal Bouallegue; Faouzi Horchani; Fatma Souissi; Mohamed Tebini; Karima Jalali; Hela Ben Ahmed; Zouhaier Abbes; Haythem Mhadhbi (PLoS ONE)
This study was conducted in order to test the effect of seed pretreatment or exogenous application through the rooting medium of 0.1 mM Salicylic Acid (SA) and 0.1 mM hydrogen peroxide (H2O2) on growth, nutritional behavior and some biochemical parameters (photosynthetic pigments, gas exchange parameters, oxidative stress indicators and antioxidant enzymes activities) of lentil plants (Lens culinaris) under 75 mM salt stress. Our results demonstrated that salt stress noticeably reduced shoot and root DWs by 39.01 and 42.81%, respectively, as compared to controls. This reduction was associated with a significant decrease in all photosynthetic parameters, including Chlorophyll (Chl) and carotenoid (Car), net assimilation of photosynthesis (A), stomatal conductance (gs), transpiration (E) and internal CO2 level (Ci), an accumulation of Na+ and Cl- and a decrease of K+ and Ca2+ concentrations in plant shoots and roots. In addition, relative to control plants, salt stress remarkably increased the malondialdehyde MDA and H2O2 contents especially in roots and increased GPOX and SOD activities, especially in plant shoots. Both methods of SA and H2O2 application recovered the plant growth, enhanced shoot and root DWs (increase of 67.65 and 82.36% in shoots and roots, respectively, as compared to salt-stressed plants) and increased all parameters that were reduced by NaCl treatment. Nevertheless, the most prominent effects of SA and H2O2 on plant growth were obtained with the seed priming method. Thus, SA and H2O2 applications, especially the H2O2 seed priming method, induced the antioxidant system, improved the membrane stability and ameliorated the gas exchange parameters. As compared to salt plant stressed, Na+ and Cl- contents were significantly decreased and K+ and Ca2+ were significantly increased in shoots and roots following SA and H2O2 applications, especially with the H2O2 seed priming method. Similarly, this method was more efficient in alleviating the adverse effects of salt stress on all photosynthetic pigment contents and measured gas exchange parameters. Compared to salt stressed plants, it significantly decreased the H2O2 and MDA contents and further stimulated GPOX and SOD activities. Our results indicated that the seed priming method, particularly with H2O2, could be recommended for obtaining better growth of lentil seedlings under salt-affected soil conditions.